PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS LITERASI NUMERASI PADA MATERI SKALA DAN PERBANDINGAN DI SEKOLAH DASAR - Erviona Rizky Dwirahma; Dian Kusmaharti; Via Yustitia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Numeracy literacy competency among students who are classified as low. Apart from this, in mathematics learning, some teachers only use textbooks and a lack of teaching materials to support learning, which causes a lack of student interest and monotony in mathematics learning, so teaching materials are needed that are integrated with numeracy literacy in order to grow students' numeracy literacy competencies. The aims of this research are (1) to describe the process of developing mathematics teaching materials based on numeracy literacy, (2) to determine the feasibility of mathematics teaching material products based on numeracy literacy. The development model in this research is a 4D model. There are four stages in the 4D model, including Define, Design, Development and Disseminate. However, the development research carried out only uses the 3D stage or up to the Development stage. In this development research, data collection techniques were used, namely unstructured interviews and questionnaires and used qualitative data analysis techniques and quantitative data analysis techniques. The results of the research are (1) a mathematics teaching material product based on numeracy literacy in scale and comparison material in elementary schools. Based on the results of the assessment scores obtained by experts (material experts, media experts and language experts), it was found that (2) feasibility test results for the product development of mathematics teaching materials based on numeracy literacy in scale and comparison material in elementary schools received the